Exploring the Competitive Advantage of Coffee Shops’ Locations using Spatial Big Data Based on i2SFCA and Contour Tree Technique: The Case of Incheon Metropolitan City - 김현중; 성은영; 여관현 (Korean Journal of Social Quality, 2022)
This study explores the spatial competitive structure and locational competitive advantage of coffee shops using microscopic spatial resolution. The analysis was conducted in the Incheon Metropolitan City using data from 2018. The spatial big data-based i2SFCA (Inverted Two-Step Floating Catchment Area) and contour tree methods were used to measure the locational competitive advantage. The location efficiency of individual coffee shops revealed huge disparities; Of the examined areas, Yeonsu 3-dong, Seonhak-dong, and Dowon-dong had the best location efficiency. In addition, the findings showed more competition between coffee shops in places with higher land prices. Finally, even in areas that are not close to subway stations, niche regions, where the location efficiency of coffee shops is high, were identified. Since restrictions on the use of big data are directly related to the study's limitations, follow-up studies that use consumer behavior are needed to elaborate on the location issues of coffee shops. KCI Citation Count: 0